Efeitos da Exenatida e da Sitagliptina durante a indução da periodontite em ratos - Moraes, Renata Mendonça [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Diabetes Mellitus is a high prevalent disease as well as periodontitis. The literature supports a two way relationship between them. A new class of drugs for diabetes treatment, peptide-like glucagon-1 (GLP-1) agonists and dypeptidyl peptidase-4 (DPP-4) inhibitors, has shown pleiotropic effects, like bone anabolic, antiresoptive and antiinflammatory actions. The aim of this study was to evaluate the effect of exenatide (GLP-1 agonist) and sitagliptin (DPP-4 inhibitor) during periodontitis induction in rats. Forty male rats were divided into four groups:1) exenatide group (GE): animals with induced periodontitis that received 3 μg/Kg/day of exenatide subcutaneously; 2) sitagliptin group (GS): animals with induced periodontitis that received 10 mg/Kg/day with sitagliptin orally; 3) periodontal disease group (PD) and 4) control group (CG); both treated with the drug vehicles. Periodontitis was induced by the insertion of ligature around the first molars and the drugs were administered for 28 days. On the day of sacrifice, animals were weigthed and blood were colleccted for serum analysis of GIP, GLP-1 and DPP-4. The mandibles underwent radiographic analysis for assessment of alveolar bone support, and the histological processing for histomorphometric analysis (area of bone loss in the furcation area, linear interproximal bone loss and percentage of collagen). The use of the drugs led to a lower percentage of weight gain and had no influence on glucose levels. Sitagliptin reduced the concentration of DPP-4, while exenatide had no influence on GLP-1 levels. In radiographic and histomorphometric analysis, it was proved the effectiveness of induction of periodontitis, with a significant difference of bone support, alveolar bone loss and percentage of collagen between the PD and CG. On the other hand there was no statistical difference between the test groups and PD group. In conclusion, within the parameters of this study both exenatide and ...

A diabetes mellitus e a periodontite são patologias inflamatórias prevalentes e que se agravam mutuamente. Os novos medicamentos para o tratamento da diabetes, os agonistas do receptor do peptídeo semelhante ao glucagon-1 (GLP-1) e os inibidores da enzima dipeptidil peptidase-4 (DPP-4), têm apresentado efeitos pleiotrópicos como estimulação da formação e inibição da reabsorção óssea e características anti-inflamatórias. O objetivo deste trabalho foi avaliar os efeitos do uso da exenatida (agonista do GLP-1) e da sitagliptina (inibidor da DPP-4) na periodontite induzida em ratos. Foram utilizados 40 ratos divididos em quatro grupos: 1) exenatida (GE):animais com periodontite induzida e que receberam 3 μg/Kg/dia de exenatida por via subcutânea; 2) sitagliptina (GS) animais com periodontite induzida e que receberam 10 mg/Kg/dia de sitagliptina por via oral; 3) com doença periodontal (DP) e 4) controle (GC), ambos receberam os veículos de dissolução dos medicamentos. A periodontite foi induzida pela inserção de ligadura ao redor dos primeiros molares inferiores e os medicamentos foram administrados por 28 dias. No dia do sacrifício, os animais foram pesados e foi coletado sangue para análise sorológica de polipeptídeo insulinotrópico dependente de glicose (GIP), GLP-1, DPP-4 e glicose. As hemimandíbulas foram submetidas à análise radiográfica para avaliação do suporte ósseo alveolar, e a processamento histológico para análise histomorfométrica (área de perda óssea alveolar na região de furca, perda óssea linear interproximal e porcentagem de colágeno). O uso dos medicamentos levou a menor porcentagem de ganho de peso e mas não influenciou a glicemia dos animais. A sitagliptina reduziu a concentração de DPP-4, enquanto a exenatida não aumentou os valores de GLP-1. Nas análises radiográfica e histomorfométrica, comprovou-se a eficácia da indução da periodontite, com diferença estatística entre os...
Keywords: Periodontite; Diabetes mellitus; Patologia bucal; Periodontitis